Identifikasi Senyawa Penyusun Produk Cair Hasil Pirolisis Aspal Alam dari Lawele Kabupaten Buton - Rustam Musta; Muh. Siddik Ibrahim; Laily Nurliana (Universitas Pendidikan Mandalika Mataram, 2021)
Identification of Liquid Product Compounds from Natural Asphalt Pyrolysis from Lawele, Buton Regency has been carried out. This research is intended toidentify the content of the compounds contained in the liquid fraction from the pyrolysis of Lawele's natural asphalt. This is a research experimentwith natural asphalt material was simply pyrolyzed at a temperature of 350oC with a little vacuum. The resulting liquid products were analyzed using the GC-MS instrument and analysis showed that there were 24 compounds contained in the liquid fraction resulting from the pyrolysis of Lawele asphalt with 2 main components, namely Phenol (C6H6O) of 16.45% and acetic acid (C2H4O2) of 12.47%. Another important product is alkane derivatives, namely Undekane (C11H24) and cyclo-octene (C8H14) which can be used as fuel.